Online Dispute Resolution (ODR) in the Digital Business Dispute Resolution System: The Problem of Regulation Fragmentation and Harmonization of the Digital Justice System in Indonesia - Ananda Gymnastiar Dwijaya; Harmono Harmono (Jurnal Legisci, 2026)
Background. The development of the digital economy has encouraged the transformation of business dispute resolution mechanisms towards the use of Online Dispute Resolution (ODR) as a technology-based dispute resolution instrument. In Indonesia, ODR is developing progressively through various sectoral regulations, such as electronic court mediation, a dispute resolution system for the financial services sector, and an internal dispute resolution mechanism on e-commerce platforms. However, these developments have not been followed by adequate regulatory harmonization and institutional integration. Aims. This study aims to analyze the legal position of ODR within Indonesia's digital business dispute resolution system, identify justice and legal protection issues in ODR practice, and formulate an ideal, harmonized framework for the digital justice system. Methods. This study employs a normative juridical method, using a legislative and conceptual approach. Result. The results of the study show that the main problem of ODR in Indonesia no longer lies in the absence of law, but in the fragmentation of regulations, weak interoperability between digital dispute resolution institutions, and the dominance of private platforms that have the potential to give birth to algorithm-based automated private justice without adequate supervision. Conclusion. The lack of synchronization between ODR and the personal data protection regime, and the absence of an AI Governance framework, show that the digitalization of dispute resolution cannot fully guarantee digital justice. Implementation. It is necessary to harmonize regulations by developing an ODR system interoperable with e-Court, BPSK, and other dispute resolution institutions, accompanied by the standardization of private ODR operators and the strengthening of artificial intelligence governance in the Indonesian legal system.